PENERAPAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA PADA PABRIK PAKAN TERNAK DI KOTA MEDAN - Delvika, Yuana (Jurnal Sistem Teknik Industri, 2017)
The increasingly globalized changes in the modern economy have grown rapidly in all areas of life such as industry, services, property, mining, transportation and others. But behind the progress there is a price to be paid by the people of Indonesia is the negative impact caused one of them is a disaster such as accidents, pollution and occupational diseases that resulted in thousands of people injured every year. This condition is caused by the lack of concern about safety and health (K3) in the community. Health and Safety Management System (SMK3) is regulated in Government Regulation No. 50 of 2012 on Guidelines for Implementation of Occupational Safety and Health Management System. HSE Management System is part of the overall corporate management system required for the development, implementation, achievement, assessment and maintenance of OSH obligations, in the context of risk control related to work activities for the creation of safe, efficient and productive workplaces.This research was conducted at a company that produce animal feed in Medan City. The company is building a health and safety management system in the company.The result of research on the implementation of Occupational Safety and Health Management in animal feed companies that the implementation of SMK3 in the company has followed the clauses required in PP No.50 of 2012. This is shown by the small gap between Government Regulation No.50 of 2012 with the application in company.